The Role of Short-Chain Fatty Acids of Gut Microbiota Origin in Hypertension - Wu, Yeshun; Xu, Hongqing; Tu, Xiaoming; Gao, Zhenyan (Frontiers in Microbiology, 2021)
Hypertension is a significant risk factor for cardiovascular and cerebrovascular diseases, and its development involves multiple mechanisms. Gut microbiota has been reported to be closely linked to hypertension. Short–chain fatty acids (SCFAs)—the metabolites of gut microbiota—participate in hypertension development through various pathways, including specific receptors, immune system, autonomic nervous system, metabolic regulation and gene transcription. This article reviews the possible mechanisms of SCFAs in regulating blood pressure and the prospects of SCFAs as a target to prevent and treat hypertension.